2014
DOI: 10.4103/0971-3026.137049
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow lesions: A systematic diagnostic approach

Abstract: Bone marrow lesions on magnetic resonance (MR) imaging are common and may be seen with various pathologies. The authors outline a systematic diagnostic approach with proposed categorization of various etiologies of bone marrow lesions. Utilization of typical imaging features on conventional MR imaging techniques and other problem-solving techniques, such as chemical shift imaging and diffusion-weighted imaging (DWI), to achieve accurate final diagnosis has been highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Second, erythroid hyperplasia also contains some amount of microscopic (intravoxel) fat, which exhibits signal loss on T 1 -weighted out-of-phase images compared to in-phase images. 2,3 Retrospective review of the T 1 -weighted DIXON images indeed showed that this was also the case in the presented patient (Fig. 2).…”
Section: Introductionsupporting
confidence: 75%
“…Second, erythroid hyperplasia also contains some amount of microscopic (intravoxel) fat, which exhibits signal loss on T 1 -weighted out-of-phase images compared to in-phase images. 2,3 Retrospective review of the T 1 -weighted DIXON images indeed showed that this was also the case in the presented patient (Fig. 2).…”
Section: Introductionsupporting
confidence: 75%
“…It is often necessary to use CT for the characterization of tumors in the ribs, posterior elements of the spine, and other flat bones with a higher cortex/medullary bone ratio. In the case of some bones like the ribs and phalanges, CT may perform better than MRI, because of higher spatial resolution and fewer motion artifacts [ 37 ]. Owing to the higher resolution, CT also may perform better than MRI in the small bones of the hands, feet, or even in the skull.…”
Section: Primary Imaging and The Current Imaging Repertoirementioning
confidence: 99%
“…Innovations in MRI such as whole-body diffusion-weighted imaging (DWI) and chemical-shift imaging have had a tremendous impact on cancer detection and management and are being integrated into mainstream routine imaging [ 27 ]. The degree of edema on MRI is not in itself a measure of the malignant potential of a bone tumor as this may be due to secondary infection of the lesions, to a pathological fracture, or to concomitant osteoarthritis [ 27 , 37 ].…”
Section: Primary Imaging and The Current Imaging Repertoirementioning
confidence: 99%
“…Transient bone osteoporosis of the hip is usually spontaneously self-limited, AVN represents an irreversible condition possibly leading to permanent joint failure, and SIF may either completely resolve or progress towards osteonecrosis. Either conventional MRI acquisition or DwI does not always allow to differentiate these conditions [ 21 , 22 ], but significant differences are found in perfusion parameters: maximum enhancement showed higher values in the transient osteoporosis and SIF, than in the AVN group. These higher values are maybe caused by reperfusion phenomena [ 23 ] that characterize transient osteoporosis and SIF, while the lower values in AVN are probably due to inflammatory processes, fibrocystic repair [ 24 ], and granulation tissue adjacent to the necrotic marrow [ 25 ].…”
Section: Imagingmentioning
confidence: 99%